Flexibility in Power Systems of Integrating Variable Renewable Energy Sources - Wojciech Lewicki; Hasan Huseyin Coban (Journal of Advanced Research in Natural and Applied Sciences)
The issue of energy security is addressed in many publications and by specialists in many fields. None of the researchers has any doubts that renewable sources have an impact on the functioning of the power system, in particular on its reliability. The intermittent nature of renewable energy sources introduces a new type of uncertainty to the operation of power systems. The aim of the article is to present an important research problem in the relationship of a smart power grid - network flexibility - optimization models. This study focuses on the analysis of the short-term (operational) and long-term (investment) aspects of providing flexibility with sources of fossil fuel generation, storage, and demand response. The authors discussed the role of power system flexibility at the stage of generation and planning. Paying special attention to the simplified optimization and load profile effect. The proposed optimization model was implemented using the MATLAB optimization engine. The research results indicate the key role of both the identification of energy flexibility and the factors affecting it in terms of renewable development and in terms of savings in investment and operating costs. The recipients of the research may be public and local government units that plan to increase the share of renewable energy in their energy systems in the future. To ensure energy stability and reduce energy production costs.